Solid-state additive manufacturing for metallized optical fiber integration. (September 2015) - Monaghan, T.; Capel, A.J.; Christie, S.D.; Harris, R.A.; Friel, R.J.
Abstract: The formation of smart, Metal Matrix Composite (MMC) structures through the use of solid-state Ultrasonic Additive Manufacturing (UAM) is currently hindered by the fragility of uncoated optical fibers under the required processing conditions. In this work, optical fibers equipped with metallic coatings were fully integrated into solid Aluminum matrices using processing parameter levels not previously possible. The mechanical performance of the resulting manufactured composite structure, as well as the functionality of the integrated fibers, was tested. Optical microscopy, Scanning Electron Microscopy (SEM) and Focused Ion Beam (FIB) analysis were used to characterize the interlaminar and fiber/matrix interfaces whilst mechanical peel testing was used to quantify bond strength. Via the integration of metallized optical fibers it was possible to increase the bond density by 20–22%, increase the composite mechanical strength by 12–29% and create a solid state bond between the metal matrix and fiber coating; whilst maintaining full fiber functionality.